(untitled) (Journal of the College of Basic Education, 2026)
This research aims to analyze the content of the art teacher’s guide for primary schools in Iraq according to the requirements of aesthetic education and the development of artistic appreciation. It also seeks to determine the extent to which the guide includes the basic requirements of aesthetic education and the elements of developing artistic appreciation. The descriptive-analytical approach was used as the methodology for the study, and the study relied on a content analysis checklist as the primary tool for evaluating the guide’s content according to five main axes: aesthetic educational objectives, educational activities that support artistic appreciation, methods of artistic assessment, the use of artistic media and materials, and linking lessons to the environmental and cultural context. The analysis extends to additional axes to cover all elements of aesthetic education.The results showed that most elements of aesthetic education and artistic appreciation are present in the guide, ranging from 74% to 92%, with clear weaknesses in: Individual assessment of students’ artistic expression Connection to the local cultural and heritage environment Use of modern and innovative media and materials Promoting critical thinking and artistic analysis of artworks. Based on the results, the research concluded that the teacher’s guide largely achieves the objectives of aesthetic education, but needs strengthening in some aspects to ensure the integration of the art education process. Among the most prominent recommendations are: developing the guide’s content to include critical thinking, enhancing activities related to the local environment and culture, expanding art assessment methods to include individual and creative evaluation, and using innovative media and materials. The research also suggested conducting future applied studies to evaluate the guide’s impact after its development and establishing training programs for teachers to support aesthetic education and develop students’ artistic appreciation.